RELIGIOUS ECOTOURISM POTENTIAL OF SOUTH COASTAL COMMUNITIES, WEST SUMATERA, INDONESIA - Hanafi, Beni Putra; Yuliani, Tri; Deswita, Deswita (Universitas Islam Negeri Raden Intan Lampung, 2023)
This research was motivated by the viral issue circulating on social media about a mosque floating on water and attracting the attention of tourists from more than 300 congregations with all the advantages (natural resources and human resources) that support it so that it becomes a tourist icon in Pesisir Selatan Regency. The aims of this research are: 1) to describe the potential of floating mosques for religious ecotourism owned by Pesisir Selatan Regency; 2) to analyze the role of the community in developing the potential of floating mosques as ecotourism. This research method uses qualitative descriptive analysis with a field survey approach, in-depth interviews, and observation methods with analytical techniques in this view including three activity streams, namely data reduction, data presentation, and concluding B. Milles and Huberman. Sampling was carried out using a purposive sampling technique. The research results show that there are government programs that are still hampered by political interests that have not yet been completed. The floating mosque with a Malay Arabic design relies on the natural beauty around the beach to provide a spiritual sensation that soothes the soul of every visitor. The floating mosque is a religious tourism icon that is worth visiting.